Analisis Konsistensi Putusan Hakim terhadap Perjanjian Nominee atas Hak Milik Tanah di Wilayah Indonesia antara Warga Negara Asing (WNA) dan Warga Negara Indonesia (WNI) - Imelda Martinelli; Lavienda William; Yessa Milianty (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Based on the legal provisions in the Law of the Republic of Indonesia Number 5 of 1960 concerning Basic Agrarian Principles, foreign nationals are not allowed to hold ownership rights over land in Indonesia. However, this restriction on land ownership does not prevent foreign nationals from making various efforts to still own land in Indonesia. Many cases have been found where foreign nationals (WNA) and Indonesian nationals (WNI) enter into nominee agreements (using a proxy) based on the principle of freedom of contract to circumvent the prevailing law. The main research object of this scientific writing is the consistency of judges' decisions in adjudicating nominee agreements by comparing various rulings, namely, Adjudication No. 259/Pdt.G/2020/PN.Gin, Adjudication No. 872/Pdt.G/2020/PN.Dps, and Adjudication No. 271/Pdt.G/2019/PN.Dpk. The research method used is normative juridical research with a qualitative approach. The results of the study concluded that nominee agreements entered into by foreign nationals and Indonesian nationals for land ownership in Indonesia constitute a form of legal evasion, rendering such agreements invalid and null and void by law. This is because Indonesian agrarian law establishes the principle that land and property ownership must be clear and transparent, and prohibits foreign nationals from owning land in Indonesia. It is hoped that the government will enact regulations prohibiting the practice of nominee agreements to enforce the applicable laws.